A Pharmacogenomic Study to Predict Reverse Remodeling - Afies, Mohammad (Al Makki Publisher, 2025)
Cardiac remodeling refers to structural, functional, and molecular changes in the heart in response to stress or injury. These alterations, involving both cellular and interstitial changes, contribute to the progression of heart disease. Long-term activation of the autonomic nervous system (ANS) exacerbates these changes, leading to systemic vasoconstriction, sodium and water retention, and ventricular remodeling, which accelerates disease progression. Neurohormonal activation is essential in compensating for falling cardiac output in heart failure (HF), but it also plays a major role in the progression of the disease. This study explores the role of the renin-angiotensin-aldosterone system (RAA) and the sympathetic nervous system in cardiac remodeling, particularly in heart failure, and the influence of genetic factors on drug response. The research focuses on the ß2-Adrenergic Gln/Gln Receptor genotype, a key genetic variant relevant to pharmacogenomics in left ventricular hypertrophy (LVH) treatment. Using a comprehensive review of clinical and experimental data, this study highlights how genetic polymorphisms affect the pharmacokinetics and pharmacodynamics of drugs such as beta-blockers, ACE inhibitors, and ARBs. The findings indicate that while the ß2-Adrenergic Gln/Gln Receptor genotype significantly influences drug efficacy, the challenges in applying personalized treatments based on genetic data require significant time and cost investments. The study's implications emphasize the need for personalized therapies and enhanced pharmacogenomic research to improve treatment outcomes in heart failure management, particularly in drug response and disease progression.